Ax + c = R (subtract c from each side)
Ax + c - c = R - c
Ax = R - c (divide A from each side)
Ax/A = (R-c)/A
x = ![\frac{R-c}{A}](https://tex.z-dn.net/?f=%20%5Cfrac%7BR-c%7D%7BA%7D%20)
<-answer
Answer:
x=-10/23
Step-by-step explanation:
-23x=10
x=10/-23
x=-10/23
Answer:
12.7m
Step-by-step explanation:
The equation for motion to be used to find how far the water travels is
xf = xi + Vix(t) + 1/2axt^2
xf = 0 + ViCos α(t) + 0
xf = ViCosα(t)
xf = 12 Cos 30°(t)
xf = (6√3)t
To find the total times we will use the vertical displacement equation
yf = yi + Viy(t) + 1/2ayt^2
0 = 0 + ViSinα(t) + (1/2 * (-9.8)t^2)
0 = 12Sin30°(t) - 4.9t^2
4.9t^2 = 12Sin30°(t)
4.9t^2 = 6t
Divide through by t
4.9t = 6
t = 6/4.9
t = 1.22secs
Put t = 1.22 into (6√3)t
xf = 6√3 * 1.22
xf = 12.7m
Answer:
x = 12
Step-by-step explanation:
5x - 30 = 2x + 6
3x = 36
x = 12
Observation : No two such factors can be found !!
Conclusion : Trinomial can not be factored
<span>Equation at the end of step 2 :</span> 6x2 - x - 4 = 0 <span>((2•3x2) - x) - 4 = 0
</span><span>Step 2 :</span>Trying to factor by splitting the middle term
<span> 2.1 </span> Factoring <span> 6x2-x-4</span>
The first term is, <span> <span>6x2</span> </span> its coefficient is <span> 6 </span>.
The middle term is, <span> -x </span> its coefficient is <span> -1 </span>.
The last term, "the constant", is <span> -4 </span>
Step-1 : Multiply the coefficient of the first term by the constant <span> <span> 6</span> • -4 = -24</span>
Step-2 : Find two factors of -24 whose sum equals the coefficient of the middle term, which is <span> -1 </span>.
<span><span> -24 + 1 = -23</span><span> -12 + 2 = -10</span><span> -8 + 3 = -5</span><span> -6 + 4 = -2</span><span> -4 + 6 = 2</span><span> -3 + 8 = 5</span><span> -2 + 12 = 10</span><span> -1 + 24 = 23
</span></span>
Observation : No two such factors can be found !!
Conclusion : Trinomial can not be factored
<span>Equation at the end of step 2 :</span><span> 6x2 - x - 4 = 0 </span>